Konteks Budaya Masyarakat Terhadap Refleksi Corporate Social Responsibility - Dewi Yuliati Indah (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2023)
Currently, the business world demands companies to control social and environmental problems caused by their activities and no longer want to be obsessed with purely economic interests. Corporate Social Responsibility (CSR) is one of the company's commitments to reduce these problems and is carried out by conserving natural resources and the environment in a sustainable manner. At the same time, a country's culture is seen as contributing to the differences in business behavior encountered in making this commitment. Therefore, this study uses CSR documentation studies with a cultural context that aims to stimulate thinking by providing insight into practices that develop in Western and Asian societies and countries. Based on the literature review, the research results show that the implementation of CSR in a cultural context is understood as a company's situational activity associated with the perceptions, values or habits of Western society and other Asian countries. In addition, practices in these societies have different orientations, resulting in different perceptions, personalities, strategies and guidelines.